EDUCATION AND SCHOOL FEEDING, THE PNAE AND ITS CONTRIBUTION TO REGIONAL DEVELOPMENT AND FAMILY FARMING IN SCHOOL MEALS IN GOIÂNIA - Ferreira , Maria Divina; Caruso, Sérgio (Seven Editora, 2024)
This article aims to understand how the National School Feeding Program (PNAE) plays a crucial role in promoting regional development, especially by encouraging family farming in the city of Goiânia. This government initiative not only ensures the provision of nutritious and quality meals for public school students, but also boosts the local economy by integrating smallholder farmers into the process of providing food for school meals. The integration of family farming into the PNAE has multiple benefits, such as providing a stable source of income for family farmers, encouraging local production, and promoting the economic sustainability of rural communities. In view of this and through a literature review, with important authors, such as Alvarez (2022), Monteiro (2017), Triches and Schneider (2010), among others, the study explores the inclusion of fresh and varied foods in school meals in order to contribute to a healthier diet for students, combating malnutrition and promoting healthy eating habits from an early age. The results reveal that in Goiânia, the implementation of the PNAE with a focus on family farming has shown significant results. This is because through public procurement policies that prioritize local producers, the program strengthens the regional agricultural sector and encourages more sustainable agricultural practices. The PNAE in Goiânia exemplifies how well-structured public policies can foster regional development and sustainability, while ensuring healthy and quality food for students. It can be a reference for other regions. DOI: https://doi.org/10.56238/sevened2024.037-074